2015
DOI: 10.1001/jamainternmed.2015.3931
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Florida’s Prescription Drug Monitoring Program and Pill Mill Laws on Opioid Prescribing and Use

Abstract: Program (PDMP) and pill mill laws are among the principal means states use to reduce prescription drug abuse and diversion, yet little high-quality evidence exists regarding their effect. OBJECTIVE To quantify the effect of Florida's PDMP and pill mill laws on overall and high-risk opioid prescribing and use. DESIGN, SETTING, AND PARTICIPANTS We applied comparative interrupted time-series analyses to IMS Health LifeLink LRx data to characterize the effect of PDMP and pill mill law implementation on a closed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
199
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(211 citation statements)
references
References 14 publications
11
199
1
Order By: Relevance
“…Consistent with previous research, changes were found to vary dramatically between states and subgroups, and were limited largely to Schedule II opioids [3][4][5][6]. In a country where opioid prescribing nearly quadrupled from 1999 to 2008, it seems likely that much larger and more broad-based declines will be necessary to move the needle significantly on OA-related overdose [7].…”
supporting
confidence: 73%
“…Consistent with previous research, changes were found to vary dramatically between states and subgroups, and were limited largely to Schedule II opioids [3][4][5][6]. In a country where opioid prescribing nearly quadrupled from 1999 to 2008, it seems likely that much larger and more broad-based declines will be necessary to move the needle significantly on OA-related overdose [7].…”
supporting
confidence: 73%
“…Th ough prescription drug abuse is an undeniable problem in the United States, this study demonstrates several shortcomings of the federal rescheduling of hydrocodone combination products. While several other state and FDA regulations show promise, there is little published data regarding the eff ectiveness of specifi c drug policies ( 4 ). With approximately 44 deaths due to prescription drug overdose each day, increased research and a multifaceted approach are essential in combating the prescription drug abuse epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Florida's legislative actions in 2010 through 2012, from crackdown on pain clinics to the establishment of its Prescription Drug Monitoring Program (which began operating in 2011 and included buprenorphine, schedule III drug), may confound the results of the analysis if this state is included. Some studies have shown that these policies had a significant effect on reducing opioid prescriptions, hospitalizations and deaths in Florida during the years of MHPAEA implementation (Rutkow et al, 2015;Kennedy-Hendricks et al, 2015). (2) As a consequence of the previously mentioned supply-side policies, drug overdose deaths and total standard doses of buprenorphine per month per 100,000 inhabitants in Florida declined compared to other states in the sample, thus a comparison with the rest of the states affected by MHPAEA might not be adequate.…”
Section: Monitoring Programs)mentioning
confidence: 99%
“…with OUD with respect to other states in America, and thus had a higher demand for MAT than others Rutkow et al, 2015;Kennedy-Hendricks et al, 2015). However, as long as these differences between states do not vary significantly over the period prior to MHPAEA's IFR implementation, a DDD analysis can still provide an estimate of the effect of this policy on buprenorphine access.…”
Section: Monitoring Programs)mentioning
confidence: 99%